Strategi Pelaksanaan Bulan Imunisasi Anak Nasional (BIAN) di Puskesmas Kota Baru Kabupaten Karawang - Beni Mulyani; Titin Eka Sugiatini (Universitas Malahayati Lampung, 2024)
ABSTRACT The Immunization Program is part of basic health services. The coverage of routine immunization for children in Indonesia has decreased since the COVID-19 pandemic broke out. To catch up with this, the Ministry of Health launched the National Childhood Immunization Month (BIAN) 2022. The achievement data for BIAN Puskesmas Kotabaru in 2022 are OPV (100.4), IPV (86.5), DPT-HB-HiB (90.6), MR (95.3). BIAN at the Kotabaru Health Center focused on MR immunization, the result was 95.3. To knowing the Implementation Strategy for the National Child Immunization Month (Bian) at the Kota Baru Health Center in Karawang Regency in 2023. The research design used is quantitative, in this study with a cross sectional approach. The population in this study were infants who carried out immunizations at the Kota Baru Health Center, Karawang Regency in February 2023, totaling 97 people. The sample in this study amounted to 30 people with random sampling technique. The type of data used in this research is primary data. The independent variables (independent) in this study are the role of the family and the role of posyandu cadres. The dependent variable (dependent) in this study is Basic Immunization Achievement. Data processing is carried out through editing, coding, scoring, tabulating, and data entry stages. Bivariate data analysis using the chi square test. The role of the family and posyandu cadres has a significant relationship with the achievement of the national child release month (BIAN) with a p value of 0.002 0.05. Health workers must be able to make the community aware besides the mother, the most important thing is that the family environment (general public) is given information regarding the importance of immunization in a complete and timely manner. Keywords: National Child Immunization Month (BIAN), Role of the Family, Role of Posyandu Cadres ABSTRAK Program Imunisasi adalah bagian dari pelayanan kesehatan dasar. Cakupan imunisasi rutin anak di Indonesia menurun sejak pandemi COVID-19 merebak. Untuk mengejar ketertinggalan itu, Kementerian Kesehatan mencanangkan Bulan Imunisasi Anak Nasional (BIAN) 2022. Data capaian BIAN Puskesmas Kotabaru tahun 2022 yaitu OPV (100,4), IPV (86,5), DPT-HB-HiB (90,6), MR (95,3). BIAN di Puskesmas Kotabaru difokuskan imunisasi MR yaitu hasilnya 95,3. Diketahuinya Strategi Pelaksanaan Bulan Imunisasi Anak Nasional (Bian) Di Puskesmas Kota Baru Kabupaten Karawang Tahun 2023. Desain Penelitian yang digunakan jenis kuantitatif, dalam penelitian ini dengan pendekatan Cross Sectional. Populasi dalam penelitian ini adalah bayi yang melakukan imunisasi di Puskesmas Kota Baru Kabupaten Karawang pada bulan Februari tahun 2023 yang berjumlah 97 orang. Sampel dalam penelitian ini berjumlah 30 orang dengan Teknik random sampling. Jenis data yang digunakan dalam penelitian ini adalah data primer. Variabel bebas (independen) dalam penelitian ini adalah Peran keluarga dan peran kader posyandu. Variabel terikat (dependen) dalam penelitian ini adalah Capaian Imunisasi Dasar. Pengolahan data dilakukan melalui tahap editing, coding, scoring, tabulating, dan entry data. Analisis data bivariat menggunakan uji chi square. Peran keluarga dan kader posyandu memiliki hubungan signifikan dengan capaian bulan imunisasi anak nasional (BIAN) dengan nilai p 0,0020,05.Tenaga kesehatan harus mampu menyadarkan masyarakat selain ibunya yang terpenting juga adalah lingkungan keluarga (masyarakat umum) diberikan informasi terkait pentingnya imunisasi secara lengkap dan tepat waktu. Kata Kunci: Bulan Imunisasi Anak Nasional (BIAN), Peran Keluarga, Peran Kader Posyandu